1998
DOI: 10.1139/z97-186
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour, brain serotonergic activity levels, and energy reserves of Arctic char (Salvelinus alpinus) within a dominance hierarchy

Abstract: The relationships between feeding activity, brain serotonergic activity level, and energy reserves in eight groups of Arctic char (Salvelinus alpinus) were evaluated using self-feeders in combination with passive integrated transponder (PIT) tags. Serotonin concentrations were measured in the brain stem, telencephalon, and hypothalamus. Energy reserves were measured, as fat levels, in muscle and mesenteric tissue. The self-feeding activity level was found to correlate positively (P < 0.05) with the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
2
35
1
1
Order By: Relevance
“…For example, given several stations delivering feed at different rates, subordinate fish might be able to sneak feeding opportunities at sites that are not attractive to hungry dominants. Similarly, if food is provided on demand over 24 hours, subordinates might be able to feed at night (Alanärä et al 1998).…”
Section: Solutions: Mitigating the Effects Of Domestication And Captimentioning
confidence: 99%
“…For example, given several stations delivering feed at different rates, subordinate fish might be able to sneak feeding opportunities at sites that are not attractive to hungry dominants. Similarly, if food is provided on demand over 24 hours, subordinates might be able to feed at night (Alanärä et al 1998).…”
Section: Solutions: Mitigating the Effects Of Domestication And Captimentioning
confidence: 99%
“…In rainbow trout (Oncorhynchus mykiss), Arctic charr (Salvelinus alpinus) and sea bass (Dicentrarchus labrax) there is a good correlation between the social rank and the number of self-feeder actuations: one or two dominant fish performed the majority of actuations (Alanärä andBrännäs 1993, 1996;Alanärä 1993, 1994;Millot et al 2008;Millot and Bégout 2009). In Arctic charr and sea bass there is a strong negative correlation between feeding demand (and/or growth rate) and brain serotonergic activity; the main neurological marker of chronic social stress in fish (Alanärä et al 1998;Di-Poï et al 2007). Thus, the assumption that the HTFs are representative of the population may not be true.…”
Section: Introductionmentioning
confidence: 99%
“…In rainbow trout (Oncorhynchus mykiss) and Arctic charr (Salvelinus alpinus) (5-15 young individuals; 2-6 kg m -3 ), a dominance hierarchy develops and a good correlation is observed between the social rank and the number of self-feeder actuations: the one or two dominant individuals displayed the highest number of actuations, whilst sub-dominants and subordinates showed a medium and low number of actuations, respectively (Alanärä andBrännäs 1993, 1996;Alanärä 1993, 1994). Moreover, Alanärä et al (1998) found a strong negative correlation between feeding demand (or growth rate) and brain serotonergic activity in groups of Arctic charr: high-triggering fish showed a higher specific growth rate and a lower brain serotonergic activity than low-or null-triggering fish. Serotonergic activity is commonly appraised by the 5-HIAA/5-HT ratio, 5-HIAA being the major metabolite of serotonin (5-HT).…”
Section: Feed Delivery Strategies and Fish Behaviourmentioning
confidence: 91%